Floral response to the Late Triassic Carnian Pluvial Episode - Zhang, Peixin; Yang, Minfang; Lu, Jing; Jiang, Zhongfeng; Zhou, Kai; Xu, Xiaotao; Wang, Ye; Wu, Li; Chen, Huijuan; Zhu, Xuran; Guo, Yanghang; Ye, Huajun; et al. (Frontiers in Ecology and Evolution, 2023)
The Late Triassic Carnian Pluvial Episode was characterized by dramatic increases in global temperature and humidity and in many terrestrial settings was accompanied by changes from arid to humid vegetation types. In this study, we review current evidence of terrestrial floral composition and distribution during the CPE and analyze spatial and temporal variation in relation to potential environmental driving mechanisms. Currently available evidence suggests the CPE was a globally significant event that triggered significant increases in the abundance of ferns and hygrophytes in terrestrial floras and freshwater algae in fluvial and lacustrine settings. These changes are linked temporally with eruptions of the oceanic plateau Wrangellia LIP. Massive release of greenhouse gasses including isotopically light CO2 during 3–4 distinct pulses of Wrangellian volcanism appears to have been the main driver of CPE climate change. Each pulse led to the enhancement of global atmospheric circulation and the hydrological cycle and resulted in changes from arid to humid conditions that affected floral abundance and composition. Increased terrestrial primary productivity in humid phases facilitated increased burial of terrestrial organic carbon, and led to the recommencement of peat accumulation, ending the “coal gap” that had persisted since earliest Triassic times. Enhanced movement of carbon from the atmosphere through the biosphere into the geosphere may have counteracted the warming effects of Wrangellia volcanic greenhouse gas emissions, and ultimately led to the return of a steady climate state that terminated the warm and humid conditions of the CPE.